Correlation of Vitamin D level with severity of Coronary Artery Disease(CAD) in patients of Acute Coronary Syndrome(ACS) in a Tertiary Care Centre in Western India - Cinosh Mathew1 , Nishant Saxena2 , Ashish Sharma2 , Jayesh Rawal3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background : Vitamin D deficiency (VDD) is a widespread problem in developing countries. Recentstudies have shown association of Vitamin D deficiency with atherosclerosis and Coronary artery disease.This study was conducted to assess the relationship between Vitamin D and the severity of coronary arterydisease (CAD) in patients undergoing coronary angiography.Materials and methods: Consecutive patients who underwent coronary angiography for acute coronarysyndrome or effort angina were included in a descriptive cross-sectional study and their Vitamin D levelwas measured. CAD was defined as at least one vessel stenosis >50% on coronary angiography. Vitamin Dlevels were correlated to the CAG findings as to the severity and number of vessels involved and also to thetraditional CAD risk factorsResults: Vitamin D Deficiency was noted in 70.72% of the population in the study. Patients were classifiedas normal Vitamin D level(> 30ng/ml), Vitamin D insufficiency (20-30ng/ml) and Vitamin D Deficiency(<20ng/ml). Vitamin D levels had inversely correlated with significant coronary artery disease both fornumber of vessels involved and severity (p<0.001) and dyslipidemia(p=0.009). No significant associationwas found between VDD and other risk factors such as age, sex , hypertension, diabetes mellitus andsmoking.Conclusion : Vitamin D deficiency was noted in majority of the patients undergoing CAG and was foundto be significantly associated with the prevalence and severity of CAD. However studies involving largerpopulation are needed to evaluate whether supplementation with vitamin D may help in prevention ofatherosclerosis and further development of CAD.